Prolonged Progression-Free Survival with Partial Disease Regression in Advanced Metastatic Medullary Thyroid Carcinoma Treated with Vandetanib - Sravanthi Sanivarapu, MD; Zahily Sardiñas, MD; Salini C. Kumar, MD; David S. Rosenthal, MD; Wondwossen Gebre, MD; Minakshi Ramchand, MD (AACE Clinical Case Reports, 2018)
ABSTRACT: Objective: Medullary thyroid cancer (MTC), derived from thyroidal parafollicular C-cells, is a difficult treatment problem when presenting with advanced and meta-static disease. The recent addition of targeted systemic medical therapy with tyrosine kinase inhibitors has shown great promise for disease control and prolonged survival for these patients. We present a case of a young woman with such advanced disease who has had a significant and prolonged response to treatment with the tyrosine kinase inhibitor vandetanib. We wish to alert clinicians to the use of such therapy in appropriate cases.Methods: A 22-year-old woman was referred to our medical center with MTC. Having already undergone total thyroidectomy followed by external beam radiotherapy of involved left neck lymph nodes, she presented to our institution with a significant paratracheal tumor burden and extensive pulmonary metastases. She was given systemic tyrosine kinase inhibitor treatment with vandetanib.Results: The patient, suffering no significant adverse effects of therapy, has responded biochemically showing durable reductions in calcitonin, carcinoembryonic antigen, and chromogranin A, and she has had progression-free survival with a documented partial response and disease regression after 39 months of continuous therapy.Conclusion: Advanced and metastatic MTC has classically had a poor prognosis. However, the recent introduction of systemic tyrosine kinase inhibitor therapy has greatly improved the outlook for these patients. Clinicians should be alert to this advance in therapeutics for use in selected appropriate patients.Abbreviations: CEA = carcinoembryonic antigen;CT = computed tomography;MTC = medullary thyroid cancer;PFS = progression-free survival;PR = partial response;RET = RE-arranged during Transfection;SD = stable disease;VEGFR = vascular endothelial growth factor receptor